Astronomy and Architecture in the Maya Lowlands - Šprajc, Ivan; Sánchez Nava, Pedro Francisco (Journal of Skyscape Archaeology, 2017)
This article summarises recent systematic research into the use and significance of astronomical orientations in ancient Maya architecture, and shows how by applying a more rigorous methodology to a large number of orientations we were able to detect alignment patterns that shed light on the validity of former hypotheses and provide a basis for novel interpretations. Our measurements and analysis confirm that orientations to the Sun’s position on the horizon, which largely prevail, allowed the use of observational calendars composed of multiples of 13 and 20 days and were also intended to facilitate proper scheduling of agricultural activities. Further, while some buildings recorded Venus extremes, a previously unknown orientation group has been found to refer to major lunar standstill positions. Some important buildings, aside from exhibiting astronomical orientations, are aligned to prominent features of natural or cultural landscape, implying a deliberate selection of these places for their construction. Discussing some relevant contextual evidence, we argue that Maya architectural and urban planning was dictated by a complex set of rules, in which astronomical considerations and their practical uses were embedded in a broader framework of cosmological concepts.